Leiomyoma Causing Disease in a Wild Adriatic Sturgeon ( Acipenser naccarii , Bonaparte, 1836) - A. Marsella; T. Pretto; C. Samassa; P. Tedesco; F. Pascoli; L. Congiu; A. Gustinelli; F. Borghesan; A. Toffan (Journal of Fish Diseases, 2025)
The Adriatic sturgeon, Acipenser naccarii , is an endemic species to the Adriatic Sea basin classified as critically endangered according to the IUCN Red List. Limited information is available regarding the health status and diseases affecting this species, particularly in the wild. In September 2023, a post‐spawning female Adriatic sturgeon was found along the edges of the Adige River. The fish displayed abnormal swimming, cutaneous haemorrhages, extreme emaciation and died shortly after its finding. At necropsy, the stomach appeared enlarged with a firm texture and a severe restriction of the lumen due to the thickening of the gastric wall. A gastric leiomyoma was characterised by histology, and this represents the first description of such neoplasia in A. naccarii . In the intestine, a severe infestation with roundworm belonging to the phylum Acanthocephala was responsible for severe haemorrhagic enteritis. The parasites were identified as belonging to the species Leptorhynchoides polycristatus , providing the first description of such a parasite in Italy. Finally, genetic analyses were performed in order to assess genetic purity and relatedness with captive breeding stocks. The results showed that the individual did not cluster with any captive identified groups, supporting the likelihood of a pure and wild‐origin Adriatic sturgeon.